Random Dot Motion Perimetry in Patients With Glaucoma and in Normal Subjects - WALL, MICHAEL; KETOFF, KATHRYN M. (American journal of ophthalmology, 1995)
To determine whether patients with primary open-angle glaucoma have an increase in size thresholds, prolongation of reaction times, and greater localization errors to random dot motion stimuli than normal subjects. Motion perimetry, a computer graphics method of visual field testing, quantitates a subject's ability to detect a correlated shift in position of dots within a defined circular area against a background of fixed dots. We measured motion thresholds, the smallest detectable circular dot motion target, at the Humphrey 24-2 test loci. By using the subject's light-pen responses to the location of the targets, we computed motion size threshold, reaction times, and localization errors (number of pixels from where the subject touched the monitor to the target center). With motion perimetry and conventional automated perimetry, we tested one eye in each of 25 patients with primary open-angle glaucoma and 25 age-matched control subjects. We then generated total deviation pointwise probability plots for the patients with primary open-angle glaucoma. Patients with primary open-angle glaucoma had increased mean motion size threshold (P < .0001) and increased localization errors (P < .002), compared with the control subjects. With the probability plot analysis, there was good correlation of the visual field defects between the two perimetry tests. Additionally, motion perimetry identified nerve fiber bundle-like defects in 12 patients that were not detected with conventional automated perimetry. Patients with primary open-angle glaucoma had abnormal motion perception with an increase in spatial localization error.